اللغة العربية للأغراض الخاصة وللكبار في دول جنوب شرق آسيا: أيّ كتاب في ظلّ أيّ مقاربة تربوية؟ - Chik, Abdul Rahman (2015)
Arabic for specific purposes in Southeast Asia: which book and which approach? It highlights pioneering studies in the field of ASP and calls for urgent and extensive research for writing books specially designed for specific purposes either for academic or occupational purposes. Some recommendations were made for selecting books written as output of research projects and adopting few suitable approaches such as Problem Based Learning (PBL) and Task-Based Learning (TBL).